Emotional Self-Regulation in Everyday Life: A Systematic Review - Alarcón-Espinoza, Marina; Sanduvete-Chaves, Susana; Anguera, M. Teresa; Samper García, Paula; Chacón-Moscoso, Salvador (Frontiers in Psychology, 2022)
Emotional self-regulation in childhood and adolescence constitutes a growing interest in the scientific community, highlighting in recent years the need to observe its development in their daily life. Therefore, the objective of this systematic review is to characterize publications referring to the development of emotional self-regulation of people under 18 years-old, in natural contexts. Based on the PRISMA guidelines, searches are carried out in the Web of Science, Scopus and PsycINFO databases, and in Google Scholar until May 2020. After reviewing the full text of 376 publications, 14 works are selected that are observed in their extrinsic, substantive and methodological characteristics based on the GREOM and MQCOM guidelines, by two independent evaluators. Most of the studies correspond to the last 20 years, increasing the interest in observing older children, in interaction with adults and / or in different cultures. They apply mixed methodologies, not always ascribing to a low intensity design. Strengths are observed regarding the collection and analysis of the quality of the data; and weaknesses related to the failure to record the duration and sequence of behaviors, highlighting the use of guidelines as guides for future research.